Adult learners’ perceptions of transformational educational leadership in enhancing access to adult education in Nigerian higher institutions - Jamiu Temitope Sulaimon; Moses Adeleke Adeoye; Lawal Mustapha Mohammed (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
Access to quality adult education remains a persistent challenge in Nigeria, despite policy initiatives promoting lifelong learning and flexible higher education pathways. Adult learners frequently encounter socio-economic, institutional, and logistical barriers that hinder access, participation, and programme completion. This study examined the influence of transformational educational leadership on adult learners’ access to, participation in, and satisfaction with adult education programmes in Nigerian higher institutions. Focusing on postgraduate students in the Faculty of Education at the University of Ilorin, the study targeted a diverse population of working adults balancing academic, professional, and family responsibilities. A descriptive survey research design was employed, with data collected through a structured questionnaire administered to 185 respondents. Descriptive statistics were used to address the research questions, while Pearson Product–Moment Correlation was applied to test the hypothesis at a 0.05 significance level. The findings indicated that adult learners perceived transformational educational leadership as highly effective in enhancing access, participation, and satisfaction. Key leadership practices—such as clear vision articulation, individualised consideration, intellectual stimulation, and flexible programme delivery—emerged as significant enablers of learner engagement. The correlation analysis revealed a strong positive relationship between transformational leadership and learners’ satisfaction (r = 0.651, p < 0.05). The study concludes that transformational educational leadership plays a critical role in fostering inclusive, motivating, and supportive learning environments for adult learners. This research contributes to educational leadership literature by demonstrating the learner-centred impact of transformational leadership and offers practical implications for institutional leaders and policymakers seeking to improve access, retention, and equity in adult education within Nigerian universities.